PENGARUH LABA AKUNTANSI DAN GOOD CORPORATE GOVERNANCE TERHADAP RETURN SAHAM PERUSAHAAN PESERTA CORPORATE GOVERNANCE PERCEPTION INDEX - Mawar Suci Nursetyo Yatmi, Dewi Saptantinah Puji Astuti & Bambang Widarno (Universitas Slamet Riyadi, 2016)
Stock return was expected investor when invested. Investor must be rate of company that have a good performance so their return stock is high. Purpose of this study was to determine the effect of accounting earnings and good corporate governance on stock return of corporate governance perception index’s company. The study was conducted at listed company in corporate governance perception index and Indonesia Stock Exchange 2011-2014. Sample was determined by purposive sampling method, and found 10 companies as sample in this study. Data was processed using by multiple linear regression. Test of hypothesis that variable accounting earnings has a positive significant on stock return. Variable Good Corporate Governance has a positive and no effect on stock return.Keywords: accounting earnings, Good Corporate Governance, stock return